Problems pharmacists face in the community pharmacies during the dispensing process - A perspective through the rational drug use [Serbest eczanelerde i̇laç sunumu sürecinde karşilaşilan sorunlar: Akilci i̇laç kullanimi yönünden deǧerlendirme*] - (:unkn) unknown (My University, 2009)
Health professionals have important roles in promoting rational use of drugs which is a growing concern in countries worldwide. In many countries the pharmacist has a changing role as patient counsellor/educator and as an intermediate to affect patient outcomes in the ambulatory settings. Thus, pharmacists have an important role in the safe and effective use of pharmaceuticals by providing sufficient and accurate information to the patient, and monitoring the drug therapy. However, pharmacists face many problems during the dispensing process. The current paper reviews the problems under 4 headings i.e. problems related to the prescription, the prescriber, the patient and the pharmacist.
Keywords: Drug dispensing; Patient; Pharmacist; Prescriber; Prescription; Problem; Rational drug use